Psoriasis Is Associated With Myosteatosis but Not Sarcopenia: A Case-Control Study - Chen, Xiaomei; Xiang, Hongmei; Tan, Lingling; Zhou, Jie; Tang, Jing; Hu, Xiaoyi; Yang, Ming (Frontiers in Medicine, 2021)
Background: The link between psoriasis and body fat (or obesity) has been well established. However, there are no reports detailing the possible relationship between psoriasis and fat infiltration in skeletal muscle, also known as myosteatosis. A recent study reported the possible association between psoriasis, arthritis, and sarcopenia (the loss of skeletal muscle mass or function). The present study aimed to explore the possible associations of chronic plaque psoriasis with myosteatosis and sarcopenia. Methods: We conducted a case-control study. In-patients with chronic plaque psoriasis were retrospectively recruited. Healthy controls were prospectively and continuously recruited. Unenhanced cross-sectional chest computed tomography images at the 12th thoracic vertebral level were analyzed using Mimics software. Skeletal muscle area (SMA), skeletal muscle radiodensity (SMD), and intermuscular adiposity tissue (IMAT) were measured. The skeletal muscle index (SMI) was calculated as SMA/height2. The percentage of IMAT (IMAT%) was calculated as IMAT/SMA × 100%. Myosteatosis was defined by SMD or IMAT%, whereas sarcopenia was defined by SMI. Propensity score matching was performed to adjust for the main confounders. Logistic regression models were used to evaluate the associations of psoriasis with myosteatosis and sarcopenia. Results: We included 155 psoriasis patients and 512 healthy controls. After propensity score matching, we retained 310 controls. The prevalence of sarcopenia was not significantly different between the psoriasis and control groups (men: 9.8% vs. 14.4%, p = 0.244; women: 7.0% vs. 11.7%, p = 0.548). Psoriasis patients were more prone to SMD-defined myosteatosis (men: 39.3% vs. 20.8%; women: 46.5% vs. 16.0%; both p < 0.001) and IMAT%-defined myosteatosis (men: 21.4% vs. 12.5%, p = 0.034; women: 46.5 vs. 28.7%, p = 0.042) than the control group. After adjustment for potential confounders, psoriasis was not significantly associated with sarcopenia (odds ratio [OR] 0.51, 95% confidence interval [CI] 0.25–1.19, p = 0.136). However, psoriasis was associated with SMD-defined myosteatosis (OR 3.16, 95% CI 1.86–5.37, p < 0.001) and IMAT%-defined myosteatosis (OR 1.76, 95% CI 1.04–3.00; p = 0.037). Conclusions: Chronic plaque psoriasis is independently associated with myosteatosis but not sarcopenia. Since fat and muscle are considered endocrine organs and can drive the inflammatory process, further studies detailing the interaction between psoriasis, fat, and skeletal muscle are warranted.